Peran Budaya Organisasi Dalam Meningkatkan Mutu Pendidikan Di SMP Nu Al Islami Pesanggaran Banyuwangi - Andrea Arifiyanto; Siti Aimah (Journal on Education, 2025)
This study aims to analyze the role of organizational culture in improving the quality of education. The main focus of the research is to analyse how Islamic values, norms and practices of organizational culture are applied in the school environment and to what extent they contribute to the achievement of educational quality. This research uses a qualitative approach with a case study design to understand the application of Islamic value-based organizational culture. Data were collected through observation, in-depth interviews and documentation from principals, teachers and students. Data analysis was conducted systematically through reduction, presentation, and verification of findings. The results show that a strong organizational culture plays an important role in creating a positive learning environment, supporting teacher professionalism, and increasing participation and ownership. The application of the values of collaboration, religiosity and active participation builds a conducive learning atmosphere, shapes student character and strengthens the synergy of school members. Management support through regular training and awards improves teachers' competence, while a participatory culture strengthens the active involvement of all school members. The findings confirm that an Islamic value-based organizational culture creates an inclusive and sustainable education ecosystem, contributes significantly to education quality and supports the achievement of long-term holistic education goals.